Конкурентоспособность и управление развитием национальной и региональной экономики: синтез иерархического и институционального анализа - Bazueva, Elena Valeryevna; Zhulanov, Eugene Evgenyevich; Karlina, Tatyana Valeryevna; Kovaleva, Tatyana Yuryevna; Mirolyubova, Tatyana Vasilievna; Shults, Dmitriy Nikolaevich (Вестник Пермского университета. Серия «Экономика» = Perm University Herald. ECONOMY, 2016)
Дается обзор теоретико-методологических, методических и прикладных выводов и результатов, полученных в рамках научной школы «Конкурентоспособность и управление развитием социально-экономических систем: синтез иерархического и институционального моделирования социально- экономических систем», основателем которой является проф. Юрий Калманович Перский. Центральным звеном исследований, проведенных пермскими учеными-экономистами, выступает проблематика межуровневого анализа социально-экономических систем на основе иерархического и институционального подходов. Предлагаемый инструментарий аргументированно показывает значимость изучения иерархических и институциональных взаимосвязей, игнорируемых традиционной неоклассической теорией, и необходимость системного исследования проблемы конкурентоспособности и управления в аспектах экономической иерархии: нано-, мини-, микро-, мета-, мезо-, макро-, мегауровень. Ключевыми элементами, которым уделяется основное внимание в рамках исследований научной школы, являются целостная модель иерархической экономики с учетом межуровневого взаимодействия и институционального строения; моделирование прямых, обратных, вертикальных и горизонтальных взаимосвязей, их типология и оценка влияния на разных уровнях иерархии; совершенствование государственной экономической политики; вопросы асимметричности распределения и циркулирования информационных потоков, их оптимизация; проблема гармонизации интересов участников экономических отношений и др. Особо выделен региональный вектор исследований пермских ученых, посвященный разработке теории, методологии и практики развития экономики региона в целях совершенствования региональной экономической политики. В частности, приведены результаты идентификации и оценки кластеров в экономике региона, обоснована настоятельная необходимость формирования целостной модели кластерного пространственного развития территории, изложены направления выращивания конкурентоспособной инновационной системы в регионе, показаны возможности моделирования процессов стратегического управления и реализации эффективной внешнеэкономической деятельности и развития рыночной инфраструктуры региональной экономики. Следовательно, синтез иерархического и институционального анализа позволил выстроить методологический и методический фундамент исследования иерархически устроенных национальной и региональной экономик, отдельных предприятий, отраслей и промышленно-технологических комплексов, разработать модели товарных и ресурсных рынков, осуществить структуризацию и проектирование различных институциональных систем и социально-экономических процессов. Ключевые слова иерархический подход, институциональный подход, межуровневый анализ, институты, социально-экономические системы, конкурентоспособность, управление, эффективность, национальная экономика, региональная экономика, инновации, кластер. Список литературы 1. Afonina A.G. The economic content and mechanism of cluster development management in the region's economy. Abstract of Cand. econ. sci. diss. Perm, 2012. 24 p. (In Russian). 2. Akhmetova M.I. Analysis of mechanisms of hierarchical interaction of innovation and investment companies. Proc. 1st Rus. Sci. Symp. on regional economy. Ekaterinburg, Institute of Economics of the Ural Division of the RAS Publ., 2011, vol. 2, pp. 11–14. (In Russian). 3. Akhmetova M.I. Analysis of the mechanisms of interaction between the subjects of a venture investment system. Innovative development of Russian economy: institutional environment. Proc. 4th Intern. Sci. Conf. Ed. by V.P. Kolesov, L.A. Tutova. Moscow, MAKS Press Publ., 2011, vol. 4, pp. 246–257. (In Russian). 4. Akhmetova M.I. Mechanisms of hierarchical interaction of research universities, innovation and investment companies in a venture business system. The financial and economic problems of the modern economy: collected articles. Perm, Perm National Research Politechnic Univ. Publ., 2012, pp. 5–21. (In Russian). 5. Akhmetova M.I., Persky Yu.K. Formation of the region’s innovative system: hierarchical approach. The university and the real business, 2015, vol. 1, pp. 230–235. (In Russian). 6. Bazueva E.V. Determinants of the quality of the institutional environment (a case study of gender power institutions). Economic analysis: theory and practice, 2012, no. 9, pp. 17–29. (In Russian). 7. Bazueva E.V. Econometric analysis of the relationship between the performance of the national economy and gender inequality. Moscow University Economics Bulletin, 2013, no 2, pp. 71–84. (In Russian). 8. Bazueva E.V. Institutional analysis of the system of gender power. Economic analysis: theory and practice, 2011, no. 19, pp. 9–20. (In Russian). 9. Bazueva E.V. Institutional roles of economic agents in the system of using human capital in the Russian labor market. Vestnik of Astrakhan State Technical University. Series: Economics, 2015, no. 2, pp. 22–32. (In Russian). 10. Bazueva E.V. International experience of developing a system of gender power institutions of the egalitarian type. Social research, 2015, no. 5, pp. 102–109. (In Russian). 11. Bazueva E.V. Methods of selecting an effective strategy for institutional changes (a case study of the system of gender power institutions). Proceedings of the Donetsk National Technical University. Series: Economics, 2014, no. 1, pp. 37–48. (In Russian). 12. Bazueva E.V. On the influence of institutions of gender power on the results of the modern economy’s functioning. Perm University Herald. Economy, 2012, no. 2, pp. 75–90. (In Russian). 13. Bazueva E.V. The human capital of the Perm region: gender peculiarities of realization. Economy of the region, 2010, no. 2, pp. 60–71. 14. Bazueva E.V. The peculiarities of establishment of egalitarian gender power institutions in Poland: lessons for Russia. A person, community, management, 2014, no. 2, pp. 55–72. (In Russian). 15. Bazueva E.V. The system of gender power institutions of the egalitarian type in Russia: on the trajectory of development. Ars Administrandi, 2015, no. 2, pp. 16–35. (In Russian). 16. Bazueva E.V. Transformation of gender power disposition in modern families as a driving force of institutional changes. Economic and Social Changes: Facts, Trends, Forecast, 2014, no. 4 (34), pp. 148–164. 17. Bazueva E.V., Persky Yu.K. Gender economy as a hierarchical system. Journal of economic theory, 2011, no. 2, pp. 7–20. (In Russian). 18. Bazueva E.V., Persky Yu.K. On the Development of Methodology of Feministic Economics: Synthesis of Institutional Theory and Hierarchical Analysis. World Applied Sciences Journal, 2014, no. 30 (12), pp. 1776–1780. 19. Cherwitz A.R., Sullivan Ch.A. Intellectual Entrepreneurship. A vision for graduate education. Change. November/December 2002. Available at: https://webspace.utexas.edu/cherwitz/www/ie/articles.html (accessed 28.09.2015). 20. Dmitriev D.V., Kataeva Yu.V. Information asymmetry in hierarchical analysis of the interaction between concrete products and housing construction. Industrial Economics, 2010, no. 3, pp. 72–76. (In Russian). 21. Dombrowski M.A. The main prospects for the development of interregional economic relations in the Perm region. International trade and trade policy, 2009, no. 10, pp. 26–32. (In Russian). 22. Dombrowski M.A., Butorina O.V. Information analysis of regional economic processes. Economy and Entrepreneurship, 2015, no. 4–1 (57–1), pp. 310–314. (In Russian). 23. Dubrovskaya Yu.V. Analysis of institutional inefficiency of local self-governance based on the hierarchical approach. Problems of the modern economy, 2011, no. 2, pp. 68–71. (In Russian). 24. Dubrovskaya Yu.V., Persky Yu.K. Harmonization of interests of economic agents within the system of hierarchical relationships in the economy. Journal of Economic Theory, 2011, no. 1, pp. 24–37. (In Russian). 25. Hierarchical analysis of socio-economic systems: approaches, models, applications: monograph: in 2 parts. Ed. by Yu.K. Persky. Perm, Perm National Research Polytechnic Univ. Publ., 2011, Pt. I. 412 p. (In Russian). 26. Hierarchical analysis of socio-economic systems: approaches, models, applications: monograph: in 2 parts. Ed. by Yu.K. Persky. Perm, Perm National Research Polytechnic Univ. Publ., 2011, Pt. II. 322 p. (In Russian). 27. Karlina T.V. Assessment of the competitive environment in regional consumer markets for goods and services: microeconomic approach. A panorama of competition. Information analytical bulletin. Ekaterinburg, Institute of Economics of the Ural Division of the RAS Publ., 2008, no. 3, pp. 146–151. (In Russian). 28. Karlina T.V. Development of the mechanism of regulating the system of regional goods markets on the basis of the hierarchical approach. Cand. econ. sci. diss. Perm, 2010. 237 p. (In Russian). 29. Karlina T.V. Government regulation of regional goods markets on the basis of assessing the degree of their openness. Development of the mechanism of strategic crisis management of corporate entities and regional industrial policy: problems and innovations. Proc. All–Russian research and practice conf. (Perm, 12 Nov. 2009). Perm, 2009, pp. 158–162. (In Russian). 30. Karlina T.V. Identification of regional economic clusters’ nuclei on the basis of the structural changes analysis under the conditions of the economy developing in cycles. Perm University Herald. Economy, 2011, no. 4 (11), pp. 18–29. (In Russian). 31. Karlina T.V. Increasing of regional goods markets’ efficiency. Economics and property management, 2009, no. 2, pp. 45–48. (In Russian). 32. Karlina T.V. Methods of assessing development of the regional goods markets system: microeconomic approach. Regional economy: theory and practice, 2010, no. 3 (138), pp. 50–60. (In Russian). 33. Karlina T.V. Research into regional goods markets for the purposes of the region’s economic policy. Current issues of economic sciences. Proc. 4th All–Russian research and practice conf.: in 3 parts. (Part 1). Novosibirsk, CRNS – SIB-PRINT Publ., 2009, pp. 209–214. (In Russian). 34. Kleiner G.B. Evolution of institutional systems. Central Economics and Mathematics Institute RAS. Moscow, Nauka Publ., 2004. 240 p. (In Russian). 35. Knowledge management in innovative economy: Textbook. Ed. by B.Z. Milner. Moscow, Ekonomika Publ., 2009. 599 p. (In Russian). 36. Kolesnikov A.A. Synergetics and scientific cognition. Synergetics and problems of control theory. Moscow, FIZMATLIT Publ., 2004, pp. 379–398. (In Russian). 37. Komarov S., Persky Yu., Suzdaleva G. Hierarchical interaction of strategic and operational marketing as a factor of a company’s competitive and innovative development. RISC: resources, information, supply, competition, 2012, no. 2, pp. 90–94. (In Russian). 38. Konstantinov G.N., Filonovich S.R. Intellectual entrepreneurship, or the principles of gaining a competitive advantage in the new economy. Harvard Business Review. Russia, 2005. Available at: www.hbr-russia.ru (accessed 16.06.2008). (In Russian). 39. Kovaleva T.Yu. Algorithm of identification and evaluation of regional clusters. Perm University Herald. Economy, 2011, no. 4, pp. 30–40. (In Russian). 40. Kovaleva T.Yu. Comparative analysis of interpretations and models of educational clusters formation. Bulletin of Ural Federal University. Series Economics and Management, 2014, no. 4, pp. 155–163. (In Russian). 41. Kovaleva T.Yu. Diagnosis of clusters as a benchmark for the state territorial development policy. Journal of Economic Theory, 2011, no. 4, pp. 89–95. (In Russian). 42. Kovaleva T.Yu. Identification of leading branches in the economy of Perm territory as potential clusters. Economy of the region, 2012, no. 1 (29), pp. 181–186. 43. Kovaleva T.Yu. Institutional environment as a basis for development of industrial clusters. Journal of Economic Theory, 2014, no. 3, pp. 129–135. (In Russian). 44. Kovaleva T.Yu. The evolution vector for the development of institutional forms of intellectual entrepreneurship in Russia’s economy. Ivanovo State University Bulletin. Series “Economics”, 2012, no. 2, pp. 13–19. (In Russian). 45. Kovaleva T.Yu. The problem of institutional inefficiencies in the development of intellectual entrepreneurship. Bulletin of Ural Federal University. Series Economics and Management, 2009, no. 4, pp. 26–36. (In Russian). 46. Kovaleva T.Yu., Baleevskih V.G. Identification of the Educational Clusters in the Regional Economy: Theory, Methodology and Research Results (A Case Study of Perm Krai). Journal of Econometrics and Financial Management, 2014, vol. 2, no. 4, pp. 153–162. doi: 10.12691/ijefm-2-4-7. 47. Kovaleva T.Yu., Baleevskikh V.G. Modeling of educational clusters in order to determine the state policies on territorial development (a case study of the Perm region). Ars Administrandi, 2015, no. 1, pp. 28–50. (In Russian). 48. Kutergina G.V. Monitoring of formation and development of territorial production cluster: the problem of information support. Innovative economy and industrial policy of the region (ECOPROM-2015). Proc. Int. research and practice conf. Ed. by A.V. Babkin. St. Petersburg, 2015, pp. 568–576. (In Russian). 49. Kutergina G.V. Problems of assessing fiscal investment efficiency in the region. Proc. Int. research and practice conf. Peter the Great Saint- Petersburg Polytechnic University, scientific and educational center "Innovative Economy of Industry" together with the Tallinn University of Technology, Estonian Entrepreneurship University of Applied Sciences (MAINOR), with the participation of the Central Economics and Mathematics Institute of the RAS, “St. Petersburg State Polytechnical University Journal”. Ed. by A.V. Babkin. St. Petersburg, 2014, pp. 392–395. (In Russian). 50. Kutergina G.V., Ivanova O.G. Oil and gas complexes and clusters: identification and monitoring of the region's economy. Perm University Herald. Economy, 2015, no. 2 (25), pp. 99–110. (In Russian). 51. Kutergina G.V., Mingazinova E.R. Procedures for assessing and monitoring tax incentives efficiency: approaches and problems. The bulletin of the Far Eastern Federal University. Economics and Management, 2014, no. 1 (69), pp. 84–99. (In Russian). 52. Kwiatkowski S. Intellectual entrepreneurship and sustainable economic development in the post-socialist countries of Europe. Problems of the theory and practice of management, 2002, no. 3, pp. 21–27. (In Russian). 53. Loseva E.Yu., Oborina E.D., Mingaleva Zh.A. The role of institutional factors in managing regional international economic activity. Perm University Herald. Economy, 2011, no. 1(8), pp. 55–61. (In Russian). 54. Luneva E.V., Dudurkhanov A.A. Intellectual entrepreneurship as a system factor of improvement in the quality of corporate knowledge. Transport business of Russia, 2011, no. 5, pp. 85–90. (In Russian). 55. Medvedeva L. Intellectual entrepreneurship, or the principles of gaining a competitive advantage in the new economy. Social Policy and Social Partnership, 2009, no. 8, pp. 55–57. (In Russian). 56. Mingaleva Zh.A., Loseva E.Yu., Oborina E.D. The socio-economic approach to studying international economic relations of a region. Economy of the region, 2011, no. 1(25), pp. 182–187. (In Russian). 57. Mirolyubova T.V. Formation of a new model of managing a federal subject at the regional level: theoretical and methodological approach. Problems of Contemporary Science and Practice. Vernadsky University, 2008, no. 3 (13), pp. 207–213. (In Russian). 58. Mirolyubova T.V. Identification of a cluster’s boundaries as the starting point for implementing the system of economy’s state regulation at the regional level. Tomsk State University Journal, 2008, no. 314, pp. 141–147. (In Russian). 59. Mirolyubova T.V. Management of regional economy: theoretical and applied approach. LAP LAMBERT Academic Publishing, 2011. 216 p. (In Russian). 60. Mirolyubova T.V. Theoretical and methodological aspects of indicative planning of socio-economic development at the level of the federal subject. Problems of theory and practice of management, 2008, no. 8, pp. 30–40. (In Russian). 61. Mirolyubova T.V. Theoretical and methodological aspects of state regulation of economy in a federal subject. Perm, Perm State Univ. Publ., 2008. 402 p. (In Russian). 62. Mirolyubova T.V., Afonina A.G. The economic content and mechanism of managing clusters in regional economy. Perm, Perm State Univ. Publ., 2012. 183 p. (In Russian). 63. Mirolyubova T.V., Karlina T.V. Formation of the mechanism of regional economy’s hierarchical regulation. Economy and property management, 2010, no. 4, pp. 14–19. (In Russian). 64. Mirolyubova T.V., Karlina T.V., Kovaleva T.Yu. Identification of regional clusters (a case study of the Perm region). Problems of theory and practice of management, 2012, no. 6, pp. 8–19. (In Russian). 65. Mirolyubova T.V., Karlina T.V., Kovaleva T.Yu. Patterns and factors of formation and development of regional clusters. Perm, Perm State Univ. Publ., 2013. 280 p. (In Russian). 66. Nort D. Institutions, Institutional Change and Economic Performance. Transl. from Engl. by A.N. Nesterenko. Moscow, Fond ekonomicheskoy knigi «Nachala» Publ., 1997. 180 p. (In Russian). 67. Oborina E.D., Mingaleva Zh.A. Development of the strategy of a region’s international economic activity in programs of economy’s structural modernization. Perm University Herald. Economy, 2010, no. 1(4), pp. 61–66. (In Russian). 68. Oborina E.D., Mingaleva Zh.A. Management of international economic activities in the framework of structural modernization of a region’s economy (a case study of the Perm region). St. Petersburg State Polytechnical University Journal, 2010, no. 1(92), pp. 82–86. (In Russian). 69. Persky Yu., Kovaleva T. Institutional guarantee of entrepreneurship subjects’ interaction. Conference «Innovation management and corporate sustainability». Prague, 2014. Available at: http://imacs.vse.cz/pr oceedings-2014/ (accessed 01.01.2015). 70. Persky Yu.K. The competitive vector of structural transformation of economic systems: synthesis of the evolutionary, institutional and hierarchical approaches. Journal of Economic Theory, 2008, no. 4, pp. 29–40. (In Russian). 71. Persky Yu.K. Theoretical fundamentals of formation of hierarchical relationships within the system “economic entities – macroeconomic environment”. Journal of Economic Theory, 2006, no. 4, pp. 34–51. (In Russian). 72. Persky Yu.K., Dmitriev D.V. Formation of the information-economic mechanism of managing the level of information asymmetry in the regional branch market. Bulletin of the South Ural State University. Series “Economics and Management”, 2009, no. 29, pp. 66–74. (In Russian). 73. Persky Yu.K., Dmitriev D.V. Interaction and interdetermination of competition processes and information asymmetry on the regional trade market. Economy of the region, 2010, no. 1, pp. 182–187. 74. Persky Yu.K., Dubrovskaya Yu.V. Institutional support for harmonization of interests in the system of hierarchical relationships of economy. Perm University Herald. Economy, 2011, no. 1, pp. 24–36. (In Russian). 75. Persky Yu.K., Dubrovskaya Yu.V. Institutionalization of local self-governance as a factor of regional development: hierarchical approach. Perm University Herald. Economy, 2012, no. 3.1, pp. 27–34. (In Russian). 76. Persky Yu.K., Dubrovskaya Yu.V. Institutions of local self-governance as a factor in the harmonization of interests of economic entities. Perm, Perm National Research Polytechnic Univ. Publ., 2014. 200 p. (In Russian). 77. Persky Yu.K., Dubrovskaya Yu.V. Transaction costs in the system of harmonization of interests of economic entities belonging to different hierarchical levels. Izvestia of the USUE, 2011, no. 3 (35), pp. 38–44. (In Russian). 78. Persky Yu.K., Kataeva Yu.V. Formation of the institutional structure of the housing construction market in the region. Perm University Herald. Economy, 2009, no. 4, pp. 97–107. (In Russian). 79. Persky Yu.K., Kataeva Yu.V. Hierarchical interaction of subjects of the regional housing market. Economy of the region, 2008, annex to no. 2, pp. 231–241. (In Russian). 80. Persky Yu.K., Kataeva Yu.V. Local housing markets in the region: the vector of competitive development. Perm, Perm State Univ. Publ., 2010. 168 p. (In Russian). 81. Persky Yu.K., Kataeva Yu.V. Modeling of interrelations among agents of the regional housing market. Economy of the region, 2009, no. 2 (18), pp. 153–160. (In Russian). 82. Persky Yu.K., Kostareva L.V. The company and the macroeconomic environment (the basics of mesoeconomics). Perm, 2000. 104 p. (In Russian). 83. Persky Yu.K., Kovaleva T.Yu. Institutions of intellectual entrepreneurship. Perm, Perm State Univ. Publ., 2011. 163 p. (In Russian). 84. Persky Yu.K., Kovaleva T.Yu. On the essential foundations of intellectual entrepreneurship. Journal of Economic Theory, 2009, no. 1, pp. 63–75. (In Russian). 85. Persky Yu.K., Kovaleva T.Yu. Strategic imperatives for overcoming institutional inefficiencies of intellectual entrepreneurship in the Russian economy. Perm University Herald. Economy, 2009, no. 3, pp. 6–15. (In Russian). 86. Persky Yu.K., Kovaleva T.Yu. The institutional system of intellectual entrepreneurship. Schumpeter readings, 2013, no. 1, pp. 60–65. (In Russian). 87. Persky Yu.K., Petrov V.P. On the identification of hierarchical levels of economic entities in institutional economy. Journal of Economic Theory, 2006, no. 1, pp. 51–64. (In Russian). 88. Persky Yu.K., Shults D.N. Development of ideas of the hierarchical organization of economy in the history of economic thought. Perm University Herald. Economy, 2013, no. 4 (19), pp. 13–19. (In Russian). 89. Persky Yu.K., Shults D.N. Hierarchical analysis of economy: methods and models. Ekaterinburg, Institute of Economics of the Ural Division of the RAS Publ., 2008. 203 p. (In Russian). 90. Persky Yu.K., Shults D.N. Interaction of micro- and macroeconomy: hierarchical approach. Ekaterinburg, Institute of Economics of the Ural Division of the RAS Publ., 2005. 192 p. (In Russian). 91. Persky Yu.K., Shults D.N. State regulation of economy as a hierarchical system. Journal of Economic Theory, 2005, no. 2, pp. 25–46. (In Russian). 92. Persky Yu.K., Tupitsyna M.N. Analysis of credit relations in Russia: institutional and evolutionary approach. Proc. 2nd Int. research and practice conf. "Trends in the development of the global trade in the 21st century". Perm, 2007, pp. 176–183. (In Russian). 93. Persky Yu.K., Zavyalov A.Yu. On the role of innovation susceptibility in managing innovation adaptation of a regional socio-economic system (a case study of the subjects of the Russian Federation). Ars Administrandi, 2014, no. 1, pp. 27–36. (In Russian). 94. Pogudaeva M.Yu., Zabelin Yu.I. Intellectual entrepreneurship as a factor in increasing the efficiency of knowledge management. Economic Journal, 2009, vol. 16, no. 2, pp. 151–157. (In Russian). 95. Polterovich V.M. Elements of the theory of reforms. Мoscow, Ekonomika Publ., 2007. 447 p. (In Russian). 96. Salikhova Z.M. Intellectual entrepreneurship as a form of realization of intellectual capital. Economic analysis: theory and practice, 2014, no. 20 (371), pp. 44–52. (In Russian). 97. Shults D.N. Hierarchical economy, its levels and methods of their analysis. Vestnik of the Orenburg State University. Economic, natural and technical sciences, 2006, no. 10 (60), pp. 210–216. (In Russian). 98. Shults D.N. Hierarchical economy: analysis of the levels and interlevel relations. Izvestia: Herzen University Journal of Humanities and Science, 2011, no. 130, pp. 73–79. (In Russian). 99. Shults D.N. Microeconomic funding of macroeconomics and Bohr’s complementarity principle. Vestnik Instituta ekonomiki Rossijskoj akademii nauk, 2014, no. 2, pp. 157–165. (In Russian). 100. Shults D.N., Grebnev M.I. Statistical Approach to Aggregation of Production Functions. Applied Mathematical Sciences, 2015, vol. 9, no. 134, pp. 6669–6689. 101. Shults D.N., Grebnev M.I. The statistical method of production functions aggregation. Economics and Mathematical Methods, 2016, no.1. pp. 149–165. (In Russian). 102. Sukhanova P.A. A model of the regional innovation system: national and foreign approaches. Perm University Herald. Economy, 2015, no. 4(27), pp. 92–102. (In Russian). 103. Sukhanova P.A. Current innovation infrastructure of Russian national research universities in the regional innovation system: problems and solutions. Current problems of science and education, 2013, no. 4, pp. 249–257. (In Russian). 104. Sukhanova P.A. Interconnectedness of the regional innovation system and the level of the region’s competitiveness (a case study of the Volga Federal District). Perm University Herald. Economy, 2015, no. 2(25), pp. 120–126. (In Russian). 105. Tupitsyna M.N. Factor analysis of opportunistic behavior by borrowers in the credit market of the Russian Federation. Journal of Economic Theory, 2007, no. 3, pp. 175–179. (In Russian). 106. Tupitsyna M.N. Improvement of the mechanism of interaction between participants of the credit market as a factor of economic growth. Hierarchical relationships in economic systems: theoretical and applied aspects: collected articles. Perm, Perm State Univ. Publ., 2005, pp 120–130. (In Russian). 107. Vatutina L.A., Khomenko E.B. Intellectual entrepreneurship: actors, typology and infrastructure support. The global scientific potential, 2015, no. 2 (47), pp. 100–103. (In Russian). 108. Zhulanov E.E. Economic-mathematical modeling of reproductive interactions of territorial socio-economic systems: monograph. Ed. by Yu.K. Persky. Perm, Perm National Research Polytechnic Univ. Publ., 2014. 564 p. (In Russian). 109. Zhulanov E.E. Management of regional socio-economic asymmetry as a factor of economic growth. Managing large systems. Moscow, Institute of Control Sciences of the RAS Publ., 2011, iss. 32, pp. 131–154. (In Russian). 110. Zhulanov E.E. Modeling of the national socio-economic system development under the influence of the regulatory environment for international economic activity of regional industry. Economic Sciences and Humanities, 2014, no. 4 (267), pp. 95–104. (In Russian). 111. Zhulanov E.E. Stimulation of innovative activity of regional markets’ participants as a factor of economic growth in the region. Journal of Economic Theory, 2007, no. 1, pp. 123–142. (In Russian). 112. Zhulanov E.E. Theoretical and methodological approach to measuring the results of the hierarchical management of regional socio-economic systems. Economy and Entrepreneurship, 2014, no. 2 (43), pp. 53–59. (In Russian). 113. Zhulanov E.E., Persky Yu.K. Interaction of the state and the region's industrial complex: models of hierarchical analysis and control. Ekaterinburg, Institute of Economics of the RAS Publ., 2010. 357 p. (In Russian). 114. Zhulanov E.E., Persky Yu.K. Reproduction contour of a municipality as a management model. Ars Administrandi, 2013, no. 1, pp. 5–26. (In Russian).